2022
DOI: 10.1177/08982643221074857
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Social Isolation, and All-Cause Mortality in a Large Sample of Older Adults

Abstract: Objectives Using data from a large random sample of U.S. older adults ( N = 7982), the effect of loneliness and social isolation on all-cause mortality was examined considering their separate and combined effects. Methods The UCLA-3 Loneliness Scale and the Social Network Index (SNI) were used to define loneliness and social isolation. Cox proportional hazards regression models were performed. Results Among study participants, there were 548 deaths. In separate, adjusted models, loneliness (severe and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Thus, due to the restricted overall knowledge, our aim was to investigate the association between care degree (reflecting the need for long-term care) and loneliness as well as perceived social isolation during the COVID-19 pandemic. Since loneliness and perceived social isolation can, in turn, lead to premature death [ 8 ], knowledge about the association between care degree and these factors is of great importance. Our present study can also serve as a first base for future research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the restricted overall knowledge, our aim was to investigate the association between care degree (reflecting the need for long-term care) and loneliness as well as perceived social isolation during the COVID-19 pandemic. Since loneliness and perceived social isolation can, in turn, lead to premature death [ 8 ], knowledge about the association between care degree and these factors is of great importance. Our present study can also serve as a first base for future research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…During her conservative management, the patient required oxygen therapy and expressed excessive tiredness. A recent study by Barnes et al of nearly 8000 patients suggested social isolation and loneliness were associated with increased mortality in the elderly population [ 16 ]. After the patient’s VATS, she was removed from COVID-19 precautions and had improved functional breathing status; subsequently, she began to participate more in physical therapy and became more invested in her overall plan of care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the impacts of dementia diagnoses on caregivers are not routinely assessed, despite their profound impacts on those caregivers and their strong linkages with subsequent healthcare utilization, such as long‐term care placement. Importantly, these measures also do not capture the epidemic of social isolation and loneliness, whose importance is widely recognized in the context of the COVID‐19 pandemic and is strongly associated with health outcomes 42–44 …”
Section: Mentationmentioning
confidence: 99%
“…Effective interventions exist that address these domains 45,46 . Loneliness and social isolation both have brief, well‐validated tools that are already incorporated into screening of large patient samples 42 …”
Section: Mentationmentioning
confidence: 99%